Neurogenetic Studies on the Role of DIAP1 in Neuronal Programmed Cell Death in Drosophila - Faith V Creekmore (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2011)
The ventral Corazonin (vCrz) neurons provide a model system to study neuronal programmed cell death (PCD) in Drosophila, as they undergo caspase-dependent PCD during early metamorphosis between 1 and 7 hours after puparium formation (APF). DIAP1 (Drosophila inhibitor of apoptosis) is a key survival factor, preventing accidental cell death at the wrong stage. In response to death signals, caspase activation resulting from DIAP1 degradation is a primary cause of the PCD in many tissues. However, transgenic over-expression of the wild type diap1 gene in vCrz neurons failed to block PCD completely. This previous result suggested its role as a survival factor in the vCrz neurons. To gain definitive evidence for diap1's roles as a survival factor, two P-elements, UAS-diap1(6-3s) and UAS-diap1ΔRF, were constructed and injected into Drosophila embryos. Transgenic lines were established and crossed to a Crz-gal4 line for targeted over-expression. The result showed that this type of transgenic manipulations blocked vCrz neuronal PCD significantly, supporting the critical role of diap1 in the prevention of premature vCrz death.
Keywords: Drosophila; Genetics